Determinan Minat Penggunaan E-Wallet OVO Pada Transportasi Online Grab - Putu Diah Sintha Saraswati; I Gusti Ayu Purnamawati (Jurnal Akuntansi Profesi, 2020)
This study aimed to determining the effect of perceived usefulness, perceived ease of use, perceived of risk, reputation, and costs on interest in using OVO e-wallet for Grab online transportation customers. This type of research is quantitative research in the form of primary data obtained from questionnaires with the help of the google form media and measured using a Likert scale. The sampling technique uses the convinence random sampling method. By using 100 respondents who are people of Singaraja City who have used OVO as payment media in Grab, the data was processed using SPSS Version 20 software. The results of this study indicate that the perceived usefulness, perceived ease of use, perceived of risk, reputation, and costs have a positive and significant effect on interest use OVO e-wallet for Grab online transportation customers in Singaraja City, while risk perception has a negative and significant effect on interest in using OVO e-wallet for Grab online transportation customers in Singaraja City.